Lived Islam: colloquial religion in a cosmopolitan tradition - Reinhart, A. Kevin (Cambridge University Press, 2020)
Klappentext: "Does Islam make people violent? Does Islam make people peaceful? In this book, Kevin Reinhart demonstrates that such questions are misleading, because they assume that Islam is a monolithic essence and that Muslims are made the way they are by this monolith. He argues that Islam, like all religions, is complex and thus best understand through analogy with language: Islam has dialects, a set of features shared with other versions of Islam. It also has cosmopolitan elites who prescribe how Islam ought to be, even though these experts, depending on where they practice the religion, unconsciously reflect their own local dialects. Reinhart defines the distinctive features of Islam and investigates how modernity has created new conditions for the religion. Analyzing the similarities and differences between modern and pre-modern Islam, he clarifies the new and old in the religion as it is lived in the contemporary world"--